EFFECTIVENESS OF EXPRESSIVE WRITING FOR EMOTION REGULATION IN ADOLESCENTS - Asiva Salma; Panca Kursitin Handayani; Nurlaela Widyarini (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study aimed to assess the effectiveness of expressive writing in improving emotional regulation in adolescents with low emotional regulation. A quantitative experimental design was employed using a pre-experiment approach with a one-group pretest-posttest design. The participants were 4 adolescents (2 males, 2 females) with low emotion regulation, as measured by the Emotion Regulation Questionnaire (α=0.664). The intervention involved four stages of expressive writing: recognition, examination, juxtaposition, and application to self. The results indicated a significant improvement in emotional regulation post-intervention (t = -8.392, p < 0.05). The findings suggest that expressive writing can be an effective preventive intervention for adolescents with low emotional regulation.